A Literature Review of Stainless Steel Crown for Permanent Molars: Indications, Survival, Periodontal and Radiographic Findings - Pooya Vatankhah; Fatemeh Hashemi; Alireza Sarraf Shirazi (Journal of Dentistry)
Stainless steel crowns (SSCs) are the preferred choice for restoring primary molars with extensive caries. However, they may be indicated for permanent molars in certain cases as well. While limited research assessed different aspects of this treatment separately, this review aims to consolidate the existing literature and provide a multi-dimensional analysis of preformed metal crown restoration for permanent molars. A comprehensive search of electronic databases including Pubmed, Scopus, Web of Science, Embase, and Cochrane was conducted, and relevant studies were categorized based on specific aspects of this treatment including indications, survival rates, periodontal and radiographic findings, utilization frequency, and alternative options. The review highlights the wide range of indications for SSCs on permanent molars of children, adolescents, and even adults, along with their remarkable success rates. However, noticeable underutilization, despite their proven efficacy, was observed. Periodontal defects and marginal discrepancies were found to be the most common causes of failures.